An overview of gibberellin inhibitors for regulating vegetable growth and development - Setiawan, Erik; Budiarto, Rahmat; Hamdani, Jajang Sauman; Ghorbanpour, Mansour (Universitas Padjadjaran, 2024)
Gibberellin (GAs) promotes plant growth processes like germination, shoot elongation, root development, and flowering, while its inhibition is occasionally used in some vegetable crop practices. This paper aims to review the current literature on GAs inhibitors in practical vegetable crops and suggest future strategies for increasing yield. In some vegetable crops, inhibiting GAs with natural (abscisic acid, ethylene) or synthetic (paclobutrazol, prohexadione-Ca) regulators is key to improving yield and quality. Abscisic acid (ABA) counteracts GAs in germination and stress adaptation, while ethylene (ET) opposes GAs in senescence and growth inhibition. The application of paclobutrazol (PBZ) and prohexadione-Ca (Pro-Ca) is known to inhibit synthetic GAs, resulting in denser plants while improving plant photosynthetic efficiency, which improves crop yield. Achieving desired growth and yields with GAs inhibitors relies on precise dosing, emphasizing the importance of review studies for advancing vegetable cultivation.